ByzRev 04.2022.008: Crystal Addey, Divination and Knowledge in Greco-Roman Antiquity.: Abingdon – New York: Routledge 2021. - Freni, Giulia (The Byzantine Review, 2022)
Crystal Addey, Divination and Knowledge in Greco-Roman Antiquity. Abingdon – New York: Routledge 2021. 320 pp. – ISBN 978-1-13821299-2 (£120.00)